2012
DOI: 10.1039/c2cc18144d
|View full text |Cite
|
Sign up to set email alerts
|

α-Oligofurans show a sizeable extent of π-conjugation as probed by Raman spectroscopy

Abstract: A Raman spectroscopic analysis revealed that π-conjugation does not reach saturation at least up to the octamer in long α-oligofurans and spreads over 14-15 furan units in the polyfuran. Comparing DFT calculations with experimental results suggests that a considerable amount of HF exchange is required to reproduce computationally the observed conjugation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 26 publications
2
36
0
2
Order By: Relevance
“…An additional indication of their strong conjugation is the Raman spectra of 3F-8F, in which oligofurans show a high degree of p-conjugation. [62] It is interesting to compare the above values with the typical b values reported for the rate of electron transfer (k ET ) in similar conjugated aromatic systems [63] with a range of about 0.1-0.6 À1 . [64,65] In particular, the b values obtained in this work are in agreement with those obtained from con-ductivity measurements performed on oligothiophenes (0.1 À1 ) [13] and are significantly lower than the b values obtained from conductivity measurements performed on oligophenylenes (0.35-0.57 À1 ).…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…An additional indication of their strong conjugation is the Raman spectra of 3F-8F, in which oligofurans show a high degree of p-conjugation. [62] It is interesting to compare the above values with the typical b values reported for the rate of electron transfer (k ET ) in similar conjugated aromatic systems [63] with a range of about 0.1-0.6 À1 . [64,65] In particular, the b values obtained in this work are in agreement with those obtained from con-ductivity measurements performed on oligothiophenes (0.1 À1 ) [13] and are significantly lower than the b values obtained from conductivity measurements performed on oligophenylenes (0.35-0.57 À1 ).…”
Section: Resultsmentioning
confidence: 83%
“…61 The absorption energy or dependence of the HOMO–LUMO gap on chain length is related to the degree of conjugation; thus oligofurans are slightly more conjugated relative to oligothiophenes, based on the abovementioned slope (which is in line with the β values obtained in this work). An additional indication of their strong conjugation is the Raman spectra of 3F – 8F , in which oligofurans show a high degree of π‐conjugation 62…”
Section: Resultsmentioning
confidence: 99%
“…The b value is similar for oligofurans (0.066 A À1 ) and oligothiophenes (0.070 A À1 ), thus indicating a similar extent of delocalization, despite the higher HOMO-LUMO gaps in oligofurans. [38] Computational studies suggested a slightly larger extent of delocalization in furan-bridged systems when compared with thiophene-bridged systems.…”
Section: Materials Sciencementioning
confidence: 99%
“…While both the difference in oxidation potentials and H ab depend on the energy matching between the terminal ferrocene units and the conjugated bridge, the distance decay factor (attenuation factor), b, is considered to be independent of the effect of the terminal ferrocenyl units. [38] The strongest Raman feature arising from the collective "breather" mode continuously downshifts with increasing chain length. The obtained b value for oligofurans is small relative to other conjugated systems, thus indicating strong delocalization in oligofurans.…”
Section: Materials Sciencementioning
confidence: 99%
See 1 more Smart Citation